2004
DOI: 10.1002/ps.943
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hydrophobic and hydrophilic kaolin particle films for peach crop, arthropod and disease management

Abstract: Hydrophobic and/or hydrophilic kaolin particle film treatments to peach (Prunus persica (L) Batsch) trees were evaluated for crop and pest management capabilities in six studies from 1997 to 2000. Unsprayed control and standard treatments, the latter consisting of a commercial pesticide program, were included for comparison. Treatments in initial studies were applied via handgun, which resulted in a uniform and heavy deposit of kaolin after the first application. In contrast, treatments in subsequent studies u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…Whether or not kaolin particle fi lms provide disease control, other benefi cial effects of applying such agents have been observed. For example, liquid formulations of both hydrophobic and hydrophilic particle fi lms were shown to double yields of pear in fi eld trials, while delayed fruit maturation, increased fruit size, increased fruit number and increased fruit yield were obtained following use of kaolin particle fi lms (Lalancette et al, 2005). In the latter case, the authors attributed the effects to a reduction in plant stress.…”
Section: Particle Fi Lms As Agents For Control Of 123 Plant Diseasesmentioning
confidence: 93%
See 2 more Smart Citations
“…Whether or not kaolin particle fi lms provide disease control, other benefi cial effects of applying such agents have been observed. For example, liquid formulations of both hydrophobic and hydrophilic particle fi lms were shown to double yields of pear in fi eld trials, while delayed fruit maturation, increased fruit size, increased fruit number and increased fruit yield were obtained following use of kaolin particle fi lms (Lalancette et al, 2005). In the latter case, the authors attributed the effects to a reduction in plant stress.…”
Section: Particle Fi Lms As Agents For Control Of 123 Plant Diseasesmentioning
confidence: 93%
“…on apple leaves, although it was not consistently effective against the cedar apple rust pathogen Gymnosporangium juniperi-virginianae (Thomas et al, 2004). In a recent four-year study, hydrophobic kaolin particle fi lms failed to control Cladosporium carpophilum or Podosphaera leucotricha on peach, although it did control Monilinia fructicola (Lalancette et al, 2005). In contrast, hydrophilic kaolin particle fi lms did not control any of the peach pathogens, leading the authors to suggest that hydrophobicity and deposit density may be important factors for effective disease management (Lalancette et al, 2005).…”
Section: Particle Fi Lms As Agents For Control Of 123 Plant Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ladd et al ( 1978 ) showed that extracts of neem seeds were highly repellent to adult JB, protecting sassafras and soybean leaves almost completely from JB feeding. Some commercial formulations of azadirachtin also performed well against adults on peach (Lalancette et al 2005 ) . In Florida, studies showed azadirachtin to cause low morbidity and mortality against adult JB (Vitullo and Sadof 2007a, b ) .…”
Section: Natural Insecticidesmentioning
confidence: 97%
“…Particle fi lm technology such as kaolin successfully reduced JB adults and their damage in peach (Lalancette et al 2005 ) . A disadvantage of this product is the high use rate recommended, i.e.…”
Section: Organic Adulticidesmentioning
confidence: 99%